2006
DOI: 10.1002/marc.200600534
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Catalyzed Norbornene Oligomerization. Isolation of a Crystalline Heptamer with a 2,3‐exo‐Disyndiotactic Structure

Abstract: Summary: Norbornene (NB) was oligomerized at 0 °C using AlEt2Cl‐TiCl4 at a monomer/titanium molar ratio of about 11. The oligomerization product consists of a fraction soluble in diethyl ether, amorphous by X‐ray examination, and of a crystalline fraction, insoluble in diethyl ether. The crystalline fraction was shown by powder X‐ray diffraction to consist of a NB heptamer. Single‐crystal X‐ray analysis indicated that the heptamer had a stereoregular 2,3‐exo‐disyndiotactic structure. The heptamer adopts a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Single crystal X-ray analysis indicated that the crystalline compound was a norbornene heptamer with a stereoregular 2,3-exo-disyndiotactic structure, containing a terminal ethyl group, which originates from the first monomer insertion into the Ti-Et bond of the catalyst [113] (Fig. 8).…”
Section: Titanium and Zirconium Catalystsmentioning
confidence: 98%
“…Single crystal X-ray analysis indicated that the crystalline compound was a norbornene heptamer with a stereoregular 2,3-exo-disyndiotactic structure, containing a terminal ethyl group, which originates from the first monomer insertion into the Ti-Et bond of the catalyst [113] (Fig. 8).…”
Section: Titanium and Zirconium Catalystsmentioning
confidence: 98%
“…[37] Sen and co-workers studied the addition polymerization of functionally substituted NBs and they found that the endo isomers were polymerized more slowly with respect to the exo analogues because of the coordination of the donor atom to the transition metal ( Figure 2). [38,39] Inspired by the discovery of Porri and co-workers, [34][35][36] in this work we report on the oligomerization of DCPD (mixture of endo and exo isomers), of the partially saturated dihydrodicyclopentadiene (H-DCPD) and, separately, of the endo and exo isomer catalyzed by TiCl 4 /Et 2 AlCl. Oligomers consisting of 2,3-enchained units were obtained.…”
Section: Introductionmentioning
confidence: 94%
“…[43] The crystallizing species were unambiguously found to be tetramers with a 2,3-exodisyndiotactic enchainment in the conformation sketched in Figure 5. [40] It appears highly plausible, from the way of polymerization of the corresponding monocyclic NB, [34][35][36] and the fact that DCPD tetramer has the same stereoregular 2,3-exo-disyndiotactic enchainment of the NB heptamer, [34,35] that the formation of the tetramer occurs through a vinyl-type addition oligomerization.…”
Section: Polymerization Of Endo/exo Dcpd Mixturementioning
confidence: 99%
See 2 more Smart Citations